Influence of admission categories, programme, race and residence status on MBBCh and BHSc student performance: Academic performance of 2021 students in physiology module - Mabizela, Sfiso E.; Chivandi, Eliton (Health SA = SA Gesondheid, 2025)
Background: The Medical Physiology and Biochemistry (PHSL 2004A) course is a compulsory 2nd-year requirement for the Bachelor of Medicine and Bachelor of Surgery (MBBCH) and Bachelor of Health Sciences (BHSc) programmes. A significant decline in pass rates was observed among the 2020 cohort assessed in 2021. Aim: This study aimed to investigate the influence of programme affiliation, residence status (on-campus or off-campus), admission category and race on PHSL 2004A pass rates in 2021. Setting: The study was conducted at the University of the Witwatersrand, focusing on Faculty of Health Sciences students. Methods: A quantitative approach was adopted, analysing data from 380 students (218 MBBCh; 162 BHSc). Independent samples t-tests, one-way between-groups ANOVA and chi-square tests were employed for analysis. Results: MBBCh students achieved higher average scores (M = 60.76) compared to BHSc students (M = 47.98), demonstrating better overall performance in the course. Students living off-campus showed slightly higher pass rates (72%) than those residing on-campus (65%), although this difference was statistically insignificant. Admission category played a significant role in performance, with students admitted under the Top 40 category achieving higher scores than those admitted under the top rural and top BC categories. Conclusion: Programme affiliation and admission category significantly influenced PHSL 2004A performance, whereas residential status did not exhibit a notable effect. Contribution: This study highlights key predictors of academic performance in PHSL 2004A, offering insights that can inform targeted interventions to improve pass rates and support underperforming student groups.